Optimal Distribution of Iron to Sink Organs via Autophagy Is Important for Tolerance to Excess Zinc in Arabidopsis. (2nd February 2021) - Shinozaki, Daiki; Tanoi, Keitaro; Yoshimoto, Kohki
Abstract: Zinc (Zn) is nutritionally an essential metal element, but excess Zn in the environment is toxic to plants. Autophagy is a major pathway responsible for intracellular degradation. Here, we demonstrate the important role of autophagy in adaptation to excess Zn stress. We found that autophagy-defective Arabidopsis thaliana ( atg2 and atg5 ) exhibited marked excess Zn-induced chlorosis and growth defects relative to wild-type (WT). Imaging and biochemical analyses revealed that autophagic activity was elevated under excess Zn. Interestingly, the excess Zn symptoms of atg5 were alleviated by supplementation of high levels of iron (Fe) to the media. Under excess Zn, in atg5, Fe starvation was especially severe in juvenile true leaves. Consistent with this, accumulation levels of Fe 3+ near the shoot apical meristem remarkably reduced in atg5 . Furthermore, excision of cotyledons induced severe excess Zn symptoms in WT, similar to those observed in atg5 . Our data suggest that Fe 3+ supplied from source leaves (cotyledons) via autophagy is distributed to sink leaves (true leaves) to promote healthy growth under excess Zn, revealing a new dimension, the importance of heavy-metal stress responses by the intracellular recycling.